Kritik Sosial Dalam Haus Ohne Huter Karya Heinrich Boll - Hutagalung, Gomgom Basa (Makara Human Behavior Studies in Asia, 2004)
Wars have always brought huge negative impacts, for example: it breaks the human spirit, deeply buries traditional values and customs, and destroys morals, economy, souls, idealism and the future of the human race. Heinrich Böll, who experienced World War I and II, had been deeply concerned about the social conditions in Germany in the aftermath of the Second World War. This research tries to explain Böll’s criticism on the condition of the German society after World War II from the sociological approach. This writing explains how wars destroy morals, souls, and the human future.